MEASURING THE PROFITABILITY LEVEL OF ISLAMIC COMMERCIAL BANKS IN INDONESIA - Fauziyah Fauziyah; I Made Bagus Dwiarta; Taudlikhul Afkar; Sigit Prihanto Utomo; Teguh Purwanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to measure the level of profitability of Islamic commercial banks in Indonesia before and during the Covid-19 pandemic. This research approach uses quantitative by using paired sample t-test as a data analysis technique. The population of 14 Islamic commercial banks is also used as a research sample with saturated sampling techniques. Measures of profitability levels used are Return on Assets (ROA), return on Equity (ROE), and Net Operating Margin (NOM). The results showed that there was a significant difference in ROA before and during the Covid-19 pandemic with a downward trend. While ROE and NOM did not make significant differences despite the decline before and during the Covid-19 pandemic.